SELF-ESTEEM AND PSYCHOLOGICAL WELL-BEING IN UNIVERSITY STUDENTS - Carla Patrícia Correia Neves; Cindy Margarida Gonçalves Sousa; Maria Inês Oliveira Teixeira; Marta Isabel Ferreira Gomes; Sílvia Francisca de Sousa Monteiro (PsychTech & Health Journal)
To examine the influence of Sex, age, area of residence, academic year, health behaviors, and social media use on self-esteem and psychological well-being in a sample of Portuguese university students. A descriptive, correlational, and quantitative study was conducted using a cross-sectional, quasi-experimental design. The sample comprised 194 individuals (171 female, 23 male) aged 18-57 years. Data were collected using a sociodemographic questionnaire, the Rosenberg Self-Esteem Scale, and the Psychological General Well-being Index short version. The results showed a positive correlation between self-esteem and psychological well-being. Gender showed effects on both self-esteem and psychological well-being when associated with hours of sleep per day and social media use. Academic year and physical exercise practice only affected self-esteem. Age demonstrated statistically significant multivariate effects on both self-esteem and psychological well-being. No significant effects were found on self-esteem and psychological well-being for the remaining variables (area of residence, smoking habits, hours of sleep per day, social media use, and daily time spent on social networks). It is possible to conclude that self-esteem positively influences psychological well-being, and psychological well-being affects self-esteem, highlighting the importance of a healthy relationship between these constructs. In the absence of such a relationship, access to mental health and support services is necessary.